The image of the world through names: anthroponymy of Russian folk tales - Jalilova, Aziza (The Lingua Spectrum, 2025)
Russian folk tales are an important part of Russia's cultural heritage, reflecting national values, worldview and behavioral stereotypes of the people. The linguacultural approach considers language as a structural model of culture, where each element is correlated with ideas about the world. It is the language that forms the national picture of the world, in which: the important is highlighted (has more words and synonyms); the valuable is emphasized (through proverbs, names, epithets); the sacred is protected (taboos, euphemisms, special forms of address). The article provides a linguocultural analysis of anthroponyms - proper names of characters in fairy tales from the classic collection by A. N. Afanasyev. The names Ivan, Emelya, Vasilisa, Marya, Koschei and Baba Yaga are considered, which perform the function of not only identification, but also serve as carriers of stable cultural concepts symbolizing such qualities as simplicity, kindness, wisdom, strength, evil and trials. The work uses methods of contextual, semantic, cultural and comparative analysis. The analysis shows that anthroponyms reflect the key mental attitudes of the Russian people, form a national picture of the world, and reveal traditional values and archetypes. The results of the study have practical significance and can be used in teaching Russian as a foreign language, linguacultural studies and intercultural communication, contributing to a better understanding of national cultural characteristics.